The West African Monetary Union An Analytical Review - Bhatia, Rattan (Occasional Papers; Occasional Paper ;, 1985)
Until 1984, the West African Monetary Union (WAMU) consisted of six West African countries- Benin, Burkina Faso, Ivory Coast, Niger, Senegal, and Togo. (Mali withdrew from the Union in 1961 and rejoined in 1984; it is therefore excluded from this analysis, which deals with a period when it was not a member.).